The Oxford handbook of emotional development - Dukes, Daniel; Samson, Andrea C.; Walle, Eric A. (Oxford University Press, 2022)
Explores a range of disciplines, including, psychology, neuroscience, sociology, primatology, philosophy, history, cognitive science, computer science, and education.